Analysis of the Legal Strength of Oral Agreements in the Civil Code - Sukadana, Dewa Ayu Putri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
An agreement is a legal relationship that is often carried out in social life in society.  An agreement according to Article 1313 of the Civil Code is an act by which one or more people bind themselves to one or more other people. Without realizing it, verbal agreements are often made in social life. The goal to be achieved is to understand the provisions governing oral agreements as well as knowing and understanding the legal force of oral agreements based on the Civil Code. The legal research method used is a normative research type, the approach is legislation and a conceptual approach. Furthermore, the legal materials are sourced from secondary legal materials and primary legal materials. Primary sources are in the form of the Civil Code, while secondary sources are books and scientific journals. The results of this research are that based on the Civil Code, verbal agreements have legal force. Its legal force applies between the parties who make it. Legal force has a reciprocal element, namely the existence of an agreement. An agreement that intends to bind oneself and together in an oral agreement. The legal strength of an oral agreement is closely related to the validity of an agreement which is said to have legal force or fulfill the requirements for the validity of the agreement. An oral agreement becomes a valid agreement if it contains these two elements